Nervonic acid in infant nutrition: a forward-looking approach to enhancing neurodevelopmental outcomes - Destaillats, Frédéric; Oliveira, Manuel; Rakitsky, Walter; Zhou, Xiaoying; Parker, Leon (Frontiers in Nutrition, 2025)
Nervonic acid (24:1 n-9, NA) is a monounsaturated very long-chain fatty acid (VLCFA) that plays a fundamental role in brain development, particularly in the biosynthesis of sphingolipids and myelin sheaths. NA is present in minute amounts in human milk and despite its importance in neuronal function and cognitive development, there is currently no ingredient available for the fortification of infant nutrition products. However, recent advances in biotechnology have made it feasible to produce high NA containing oil through fermentation, presenting a significant opportunity to address this nutritional gap. This review explores the potential of NA fortification in infant nutrition products and its impact on neurodevelopment, with a specific focus on two populations: premature infants, who are at higher risk of neurodevelopmental impairments due to incomplete in utero myelination, and healthy term infants, who may experience enhanced cognitive development with improved dietary NA intake when consuming infant formula. By critically examining the scientific basis for NA supplementation, as well as the practical challenges and regulatory considerations associated with its implementation, this review aims at providing a forward-looking perspective on how this emerging ingredient could enhance infant nutrition and improve health outcomes.